PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PEMBUATAN POLA PADA SISWA KELAS XI TATA BUSANA SMK AL-MUNAWWARIYYAH MALANG - Maulida, Iva; Nashikhah, Ma’rifatun; Yuniati, Mita; Hidayati, Lutfiyah (Jurnal Socia Akademika, 2024)
SMK Al-Munawwariyyah Malang class XI Fashion Design students' learning outcomes in pattern making and learning motivation are the subjects of this study. It also seeks to ascertain the degree to which learning motivation influences learning outcomes in learning making. This research employs an ex post facto research strategy and a quantitative methodology. All SMK Al-Munawwariyyah Malang class XI Fashion Design students fashion the study's population. 22 students from SMK Al-Munawwariyyah Malang's The sample, which was selected using a saturation sampling technique, included students in class XI Fashion Design. A questionnaire provided to XI Fashion Design students as a means of collecting data for the study. The data analysis technique used was simple linear regression analysis. The results of the study showed that: 1) learning motivation affects learning outcomes in pattern making among students in class XI Fashion Design at SMK Al-Munawwariyyah Malang, with alpha (α) = 0.031 < 0.05; 2) learning motivation affects learning outcomes in pattern making among class XI Fashion Design students. students at SMK Al-Munawwariyyah Malang is 56.7%.